PERANCANGAN DAN IMPLEMENTASI PERANGKAT LUNAK PROXY TUNNEL DENGAN ENKRIPSI KUNCI SIMETRISASIMETRIS UNTUK MANIPULASI PAKET DATA - Gat Gat (STMIK PONTIANAK, 2011)
Abstracts: The authors conducted a study on wiretapping in computer networks because of it is very disturbing security and comfort in the surf. Therefore the writer create a proxy tunnel software with symmetric and asymmetric encryption as a security agent that encrypts data communications conducted. Forms of research that the author did was experimental data collection techniques onegroup posttest-pretest, the authors study variable is the security of data packets transmitted between website and browser. Design method used is the Extreme Programming with 4 ways to apply the practical development of XP, namely coding, testing, listening and designing. The result is a software design software called